Pollution status of the Sungai Skudai river system through heavy metals - Thanapalasingam, Vynavi (2005)
This study was conducted to assess the extent of heavy metal pollution in the Sg. Skudai river system. A total of 16 monitoring stations were established along the Sg. Skudai river system. Water, plants (Phragmites karka) and sediment samples were collected from the sampling points along the downstream route of the river near the industrial zones. Samplings were conducted six times over a period of 9 months from November 2000 to July 2001. Water quality parameters such as temperature, pH, DO, BOD and COD were monitored to determine their status in relation to the health of the river ecosystem. The results were then compared where possible to the recommended present Interim National Water Quality Standards for Malaysia (INWQS) and DOE Water Quality Criteria for Malaysia with respect to support aquatic life, potable water supply and irrigation. The Instrumental Neutron Activation Analysis (INAA) and Inductively Coupled Plasma-Mass Spectrometry (ICP-MS) techniques were employed for the determination of heavy metals in the samples. The method was also controlled by analyzing the reference material for National Institute of Standards and Technology (N1ST)-SRM 1572 Citrus Leaves and NIST-SRM 1646 Estuarine Sediment. Data showed a good agreement with the certified values for the elements with more than 83 % recovery. Elemental concentrations of As, Pb, Hg, Cr, Cu, Cd, Ni and Zn were measured. The trend of several pollutants in the river and the statistical analysis of the results were obtained. Then trend of heavy metals in water of the Skudai River system is Zn>Cu>Ni>Cr>As>Pb>Hg>Cd, in plants is Zn>Cr>Cu>Pb>Ni>As>Hg>Cd and in sediments is Zn>Cr>Cu>Pb>Ni>As>Hg. All results were reported between 15-20 % of the standard deviation. Correlations exist for chromium and copper from the correlation analysis between plant and water and plant and sediment. Meanwhile, arsenic and zinc showed that these metals correlate in water and sediment.